Outer retinal tubulations response to anti-VEGF treatment. Issue 6 (30th September 2015) - Espina, Mark; Arcinue, Cheryl A; Ma, Feiyan; Camacho, Natalia; Barteselli, Giulio; Mendoza, Nadia; Ferrara, Napoleone; Freeman, William R
Abstract : Aim: To review the longitudinal changes of outer retinal tubulations (ORTs) in wet age-related macular degeneration (AMD) and their response to anti-vascular endothelial growth factor (VEGF) therapy by spectral-domain optical coherence tomography (SD-OCT), and to correlate these observations with disease activity, presence or absence of fluid, and patients' demographics. Methods: Retrospective study of wet AMD eyes treated with anti-VEGF agents and showing ORTs on SD-OCT, and the patients' fellow eye with wet AMD but without ORTs. Results: Fifty-one wet AMD eyes from 31 patients diagnosed and treated for wet AMD were included in the review and analysis of data; 33 eyes showed ORTs at baseline, while 18 fellow eyes had no ORTs. During a median follow-up treatment period of 11 months, 23 eyes had stable ORTs and 10 eyes had ORT changes. Among the 10 eyes with ORTs changes, ORTs collapsed during anti-VEGF treatment in 5 eyes but then reappeared within 12 months after stopping treatment. In two eyes, ORTs increased in size during anti-VEGF treatment, while in two other eyes ORTs collapsed without any treatment. In a single eye, ORTs collapsed within 10 months of no treatment and did not reappear upon recurrence of fluid. Eyes with ORTs tended to have lower visual acuity than eyes with no ORTs due to greater disruption of the external limiting membrane in the fovea. Conclusions: ORTs documented by SD-OCT may exhibit multiple types of longitudinal changes, such as collapse, recurrence or enlargement, which could be associated with anti-VEGF treatment or spontaneous. Some ORTs may have a vascular component or may be vascular in nature, considering their response to anti-VEGF treatment, while other ORTs are likely composed only of degenerating photoreceptor cells and may collapse independently from anti-VEGF treatments.